Bmal1 integrates circadian function and temperature sensing in the suprachiasmatic nucleus - Hoekstra,M; Ness,N; Badia,Soteras A; Brancaccio,M (Proceedings of the National Academy of Sciences of USA, 2024)
Circadian regulation and temperature dependency are important orchestrators of molecular pathways. How the integration between these two drivers is achieved, is not understood. We monitored circadian- and temperature-dependent effects on transcription dynamics of cold-response protein RNA Binding Motif 3 (Rbm3). Temperature changes in the mammalian master circadian pacemaker, the suprachiasmatic nucleus (SCN), induced Rbm3 transcription and regulated its circadian periodicity, whereas the core clock gene Per2 was unaffected. Rbm3 induction depended on a full Brain And Muscle ARNT-Like Protein 1 (Bmal1) complement: reduced Bmal1 erased Rbm3 responses and weakened SCN circuit resilience to temperature changes. By focusing on circadian and temperature dependency, we highlight weakened transmission between core clock and downstream pathways as a potential route for reduced circadian resilience.